Less favoured area measure in the Netherlands: a welcome or negligible addition? - Schouten, Marleen; Gaaff, Aris; Heijman, Wim (Applied Studies in Agribusiness and Commerce, 2009)
The Less Favoured Areas (LFAs) Directive (75/268) which was introduced in 1975, was the first common European instrument of regional agricultural structural policy. LFAs are areas where agriculture is hampered by permanent natural handicaps. The major objectives were to ensure the continuation of farming, thereby maintaining a minimum population level and preserving scenic landscapes and environmentally valuable habitats. In the Netherlands, the LFA measure is used as an additional payment, to compensate farmers for negative economic effects due to the conservation of these natural handicaps. It was not implemented as a stand alone policy, but is linked to measures aiming at active nature and landscape conservation management. In this paper, the effects will be examined of the regulations aiming at the conservation of natural handicaps on farm businesses within LFAs, when comparing them to farm businesses outside LFAs, where these regulations and handicaps do not exist. The main data source that was used is the Farm Accountancy Data Network. Reference groups of farms were compiled with the use of the simple and multiple imputation approach in Stars (Statistics for Regional Studies). Both analyses were tested with the use of a parametric and a nonparametric test. When comparing the results of both analyses, it can be concluded that there is no evidence that there is a statistical difference in family farm income corrected for and not corrected for LFA payment between the LFA farm businesses and the reference groups. Based on these findings it can be concluded that the size of the compensatory allowances is small and there is no evidence that it has a significant effect on the family farm income of LFA farm businesses. The main purpose of the Dutch LFA policy is to compensate farm businesses for negative economic effects due to the conservation of natural handicaps. Although this may be true for some individual farms, based on the methods used in this paper, it appears not to be the case for the collectivity of LFA premium beneficiaries as a whole.